Chemical constituents of croton laevifolius blume bark / Ahmad Nazif Aziz - Aziz, Ahmad Nazif (2018)
Phytochemical investigation on the bark of Malaysian Croton laevifolius Blume (Euphorbiaceae) was carried out with an intention of isolating and identifying its chemical constituents. The bark was successively extracted with the non polar (hexane), medium polar (dichloromethane) and polar (methanol) organic solvents. These extracts were evaluated for cytotoxicity, anti-inflammatory and antidiabetic activities. The hexane extract showed potential cytotoxicity against MCF-7 cell line and mild cytotoxicity against A549, WRL-68, PC-3 and A375 cells while dichloromethane (DCM) extract indicated mild and selective activity against A549 and A375 only. The hexane and DCM extracts were subjected to isolation and purification using various chromatographic techniques such as Medium Pressure Liquid Chromatography (MPLC), Radial Chromatography (RC) and Recycling Preparative High Performance Liquid Chromatography (RHPLC). Structures of the chemical compounds were elucidated using various spectroscopic techniques such as UV, IR, ID-NMR ('H, 13C, DEPT and APT), 2D-NMR (COSY, HSQC, HMBC and NOESY) and mass spectrometry. This study has led to the isolation of fourteen compounds, in which seven new and one known clerodane type diterpene named crovatin, as well as one eudesmane-type sesquiterpene named crytomeridiol were isolated from the DCM extract. This is the first occurrence of cryptomeridiol in Croton species. The new diterpenes were deduced as laevifin A, laevifin B, laevifin C, laevifin D, laevifin E, laevifin F and laevifin G. Subsequently, the hexane extract yielded laevifin B, three oleanane triterpenes: /J-amyrin, /3-amyrone and acetyl aleuritolic acid; one steroid (/3-sitostenone) and one flavonoid named pachypodol.